The Color Blindness Disorders and the Role of Sex-Linked Genes - Muhammad Ainur Rosyid Ridho; Ratri Dwi Indriani (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Sex linkage is defined as the pattern of allele expression and inheritance associated with an individual's sex chromosomes. Sex-linked genes are genes located on the sex chromosomes. Genes associated with the X chromosome are referred to as X-linked genes or X chromosome genes. Color blindness is a condition in which a person is unable to distinguish certain wavelengths of light that can be differentiated by normal vision. The ratio of the index finger length (2D) compared to the ring finger length (4D) is an inherited trait influenced by sex-influenced gene expression. Patterns of baldness in humans, or androgenetic alopecia (AGA), are age-related conditions characterized by hair thinning, miniaturization, and hair loss. The objective of the research titled “Color Blindness and the Role of Sex-Influenced Genes” is to determine whether a person is color blind and to identify the genotype of each individual in a group based on the size of their index finger. The methods used include an online Ishihara test for color blindness, conducted by each subject using a prepared website. For the sex-influenced gene experiment, participants made patterns of their index, ring, and middle fingers on both hands on HVS paper, and the finger lengths were observed. The results showed that all participants were not color blind (normal), and some participants had longer index fingers, longer ring fingers, or equal lengths of the index and ring fingers.